Stability of Human Serum Albumin Loaded PLGA Nanoparticles for Protein Delivery Applications - Vidawati, Sri; Barbosa, Silvia; Taboada, Pablo; Safira, Nadhifa P. (European Journal of Applied Sciences, 2022)
Poly(lactic-co-glycolic acid) (PLGA) is one of the most effectively developed biodegradable polymers. Biodegradable polymers based on PLGA are the most common materials used to encapsulate therapeutic agents. Protein-loaded PLGA nanoparticles are generally formulated by the double emulsion method. However, the main problems associated with this method are low encapsulation efficiency proteins and instability proteins. This study report the stability of encapsulate of Human Serum Albumin (HSA)-loaded PLGA nanoparticles for protein delivery applications.